Influence of Tucupi on Enamel Surface Roughness, Microhardness, Ultramorphology and Mass Variation - Loretto SC; Sousa NWA; Ribeiro MES; Carneiro RVTSM; Chisté R; Souza Júnior MHDSE (Dove Medical Press, 2023)
Sandro Cordeiro Loretto,1 Naama Waléria Alves Sousa,1 Mara Eliane Soares Ribeiro,2 Reginna Vyctória da Trindade Souza de Melo Carneiro,1 Renan Chisté,3 Mário Honorato da Silva e Souza Júnior1 1Multifunctional Laboratory, Postgraduate Program in Dentistry, University Center of Pará, Belém, Pará, Brazil; 2Laboratory of Biomaterials, Postgraduate Program in Dentistry, Institute of Health Sciences, Federal University of Pará, Belém, Pará, Brazil; 3Faculty of Food Engineering, Institute of Technology, Federal University of Pará, Belém, Pará, BrazilCorrespondence: Sandro Cordeiro Loretto, Multifunctional Laboratory, Postgraduate Program in Dentistry, University Center of Pará, 1500 Dom Romualdo de Seixas Street. ap 602, Torre Umari, Umarizal, Belém, Pará, 66.055-200, Brazil, Tel +559198122-3477, Email sandroloretto@hotmail.comAim: The study evaluated the influence of tucupi on enamel surface roughness, microhardness, ultramorphology, and mass variation.Materials and Methods: Ninety healthy bovine incisors were divided into three experimental groups, according to the acidic challenge adopted, being: G1- tucupi, G2- cola-based soft drink, G3-distilled water. The enamel properties (surface roughness, microhardness, ultramorphology and mass variation) of all specimens were evaluated at times T0 (before any intervention), T10 (10 days after the proposed treatments), T20 (20 days after the proposed treatments) and T30 (30 days after the proposed treatments). After confirming the normality of the data (Shapiro-Wilk test), a two-way ANOVA (α = 5%) was performed, followed by Sidak post-test, with results described as mean and standard deviation.Results: The roughness means increased for all tested groups, with no statistical difference only in G3 for all evaluated times. Microhardness of all groups showed a significant decrease over the time, with the lowest average observed in G1 in T30. Considering enamel mass variation, the lowest average was in G2 at time T3, with no statistical difference only in G3 (distilled water) over the time. Regarding ultramorphology (scanning electron microscopy - SEM), only groups G1 and G2, that were exposed to acidic challenges, showed disorganization of the enamel surface layer.Conclusion: It was possible to conclude that tucupi has low pH and high titratable total acidity, being able to gradually decrease enamel microhardness, increasing surface roughness and causing loss of dental enamel.Keywords: Manihot esculenta, erosion, dental enamel, microhardness, acidity, surface properties